PEMBERDAYAAN MASYARAKAT MELALUI BADAN USAHA MILIK DESA (BUMDES) MAKARTI JAYA DI DESA BANGUN SARI KECAMATAN MANUHING KABUPATEN GUNUNG MAS - Ibie, Evy Novitasari (FISIPOL Universitas PGRI Palangka Raya, 2025)
Community Empowerment Through Makarti Jaya Village-Owned Enterprises (BUMDes) in Bangun Sari Village, Manuhing District, Gunung Mas Regency. The main problem in this research is Community Empowerment Through Makarti Jaya Village-Owned Enterprises (BUMDes) in Bangun Sari Village, Manuhing District, Gunung Mas Regency. And what factors support Community Empowerment Through Makarti Jaya Village-Owned Enterprises (BUMDes) in Bangun Sari Village, Manuhing District, Gunung Mas Regency This study aims to: (1) To find out the actual situation and describe the various problems that arise in Community Empowerment Through Village Owned Enterprises (BUMDes) Makarti Jaya in Bangun Sari Village, Manuhing District, Gunung Mas Regency. (2) To describe matters relating to the factors that support Community Empowerment Through Village-Owned Enterprises (BUMDes) Makarti Jaya in Bangun Sari Village, Manuhing District, Gunung Mas Regency. The approach used is qualitative and descriptive research type. Data collection techniques use three process activities, namely observation, interviews and documentation. While the analysis technique used in this study is data reduction, data presentation and drawing conclusions.The results of the study show that (1) Community Empowerment Through BUMDes Makarti Jaya has been implemented quite well even though the participation of the respective communities is lacking, therefore efforts are needed from the Village Government and BUMDes Managers to provide more understanding to the community about the role of BUMDes to support the community's economy in the Village Sari wake up. (2). Factors that support empowerment are the existence of capital support from the Village Government and other parties, as well as facilities and infrastructure owned by BUMDes makarti Jaya, besides that support from various parties in empowerment such as the involvement of the Regional Government.